2015
DOI: 10.1177/0885066615571533
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Findings in Posthypoxic Myoclonus

Abstract: The physical examination findings of early posthypoxic myoclonus (PHM) are associated with poor prognosis. Recent findings indicate that patients with multifocal PHM, assumed to have a cortical origin, have a comparable outcome to resuscitated patients without PHM. Generalized PHM, assumed to have a subcortical myoclonus origin, is still associated with a bad clinical outcome. It is not known whether the electroencephalographic (EEG) findings differ between the multifocal and generalized myoclonus groups nor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 23 publications
3
66
0
1
Order By: Relevance
“…Moreover, in this cohort CM was more likely present in patients with generalized PHM than in focal PHM. This result is in line with earlier studies who demonstrated that generalized PHM can arise from the cortex 5, 6, 33. These findings suggest that the clinical model of typical CM and SM phenomenology that physicians encounter in noncomatose myoclonus patients at the outpatient clinic does not apply for PHM in the first few days after resuscitation 10, 11.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, in this cohort CM was more likely present in patients with generalized PHM than in focal PHM. This result is in line with earlier studies who demonstrated that generalized PHM can arise from the cortex 5, 6, 33. These findings suggest that the clinical model of typical CM and SM phenomenology that physicians encounter in noncomatose myoclonus patients at the outpatient clinic does not apply for PHM in the first few days after resuscitation 10, 11.…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that patients with a multiple lesioned cortex (and CM) could have a worse outcome compared to patients with a singular, small brainstem lesion (and SM). In addition, studies that correlated the generalized and focal PHM phenotype to outcome found that the severity of myoclonus, and not per se the presence or absence of brainstem damage, was related to poor outcome 1, 5, 6. Yet in contrast, another finding of this study was that in patients presenting PHM within 24 h after CPR, significantly less CM occurred (Table 3).…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations